Cardiotoxicity from Capecitabine Chemotherapy: Prospective Study of Incidence at Rest and During Physical Exercise. (16th February 2022) - Lestuzzi, Chiara; Stolfo, Davide; De Paoli, Antonino; Banzato, Alberto; Buonadonna, Angela; Bidoli, Ettore; Tartuferi, Lucia; Viel, Elda; De Angelis, Giulia; Lonardi, Sara; Innocente, Roberto; Berretta, Massimiliano; et al.
Abstract: Background: Physical activity may increase the risk of cardiotoxicity (myocardial ischemia, major arrhythmias) of 5-Fluorouracil, but this risk has never been investigated for its prodrug capecitabine. Patients and Methods: One hundred and ninety-two consecutive patients undergoing capecitabine chemotherapy from December 1, 2010 through July 31, 2016 were prospectively evaluated. The baseline evaluation included electrocardiography (ECG) and echocardiography (2DE); a follow-up evaluation, including ECG and exercise stress testing (2DE in case of ECG abnormalities), was done after ≥10 days of treatment. Cardiotoxicity was suspected from ischemic ECG changes, new kinetic abnormalities at 2DE, Lown classification ≥2 ventricular arrhythmia, symptomatic arrhythmias, or positive stress test, and confirmed by a negative stress test after capecitabine washout. Results: Cardiotoxicity was diagnosed in 32 patients (16.7%): six at rest and 26 during exercise. All 32 patients had ECG abnormalities: ST-segment changes (24 patients), negative T-waves (2) and/or arrhythmias: ventricular arrhythmias (14 cases), supraventricular tachycardia (2), complete heart block (1). Eight patients had typical symptoms, 6 had atypical symptoms, 1 had syncope, 17 (53%) were asymptomatic. Cardiotoxicity was more common in patients with atypical symptoms during daily life (OR = 15.7) and in those on a therapeutic schedule of 5 days/week (OR = 9.44). Conclusion: Capecitabine cardiotoxicity is frequent, and often elicited by physical effort. Oncologists, cardiologists, and general practitioners should be aware of this risk. Active cardiotoxicity surveillance with ECG (and echocardiogram and/or stress testing in suspected cases) during therapy is recommended. Clinical Trials registration number: CRO-2010-17. Abstract : This article assesses the overall incidence of both resting and exercise-induced cardiotoxicity in patients undergoing capecitabine chemotherapy and identifies factors associated with cardiotoxicity.